2008
DOI: 10.1016/j.febslet.2008.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective properties of eckol against ionizing radiation in mice

Abstract: We have investigated the radioprotective efficacy of eckol, a component of brown seaweed Ecklonia cava, against the gamma ray-induced damage in vivo. Our results showed that eckol significantly decreased the mortality of lethally irradiated mice. The mechanisms of eckolÕs protection were found to include: an improvement in hematopoietic recovery, the repair of damaged DNA in immune cells and an enhancement of their proliferation, which had been severely suppressed by ionizing radiation. Thus, we propose eckol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 17 publications
1
61
0
1
Order By: Relevance
“…Recently, several studies have been carried out to discover radioprotective agents from natural resources such as fruit, vegetables, and medicinal plants (Park and Pezzuto 2002;Stan et al 2008), because of the toxic side effects of many synthetic compounds on human health. In particular, the Ecklonia species have been reported to exhibit radical scavenging activity (Kang HS et al 2004), anticancer activity (Thomas and Kim 2011), and hematopoietic recovery activity (Park, Ahn, et al 2008), and phlorotannin components were identified to be responsible for the biological activity. Phloroglucinol (1,3,5-trihydroxybenzene; PG), a monomeric building block of phlorotannin and a phenolic compound known to derive only from brown algae, has cytoprotective effects on oxidative stress-induced cell damage through catalase activation (Kang KA et al 2010) and radioprotective effects on intestinal crypt cells after whole-body gamma-irradiation (Moon et al 2008).…”
mentioning
confidence: 99%
“…Recently, several studies have been carried out to discover radioprotective agents from natural resources such as fruit, vegetables, and medicinal plants (Park and Pezzuto 2002;Stan et al 2008), because of the toxic side effects of many synthetic compounds on human health. In particular, the Ecklonia species have been reported to exhibit radical scavenging activity (Kang HS et al 2004), anticancer activity (Thomas and Kim 2011), and hematopoietic recovery activity (Park, Ahn, et al 2008), and phlorotannin components were identified to be responsible for the biological activity. Phloroglucinol (1,3,5-trihydroxybenzene; PG), a monomeric building block of phlorotannin and a phenolic compound known to derive only from brown algae, has cytoprotective effects on oxidative stress-induced cell damage through catalase activation (Kang KA et al 2010) and radioprotective effects on intestinal crypt cells after whole-body gamma-irradiation (Moon et al 2008).…”
mentioning
confidence: 99%
“…Many of the studies that demonstrate the antioxidant effect of ECP extract compounds have been carried out in order to present their protective effect against radioactivity (25)(26)(27)(28)(29). In the prevention of cell damage caused by radiotherapy-induced oxidative stress, polyphenol compounds have been shown to exert antioxidant effects directly by reacting with oxygen radicals or indirectly by activating enzyme systems such as catalase, superoxide dismutase, and myeloperoxidase (15,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…In the prevention of cell damage caused by radiotherapy-induced oxidative stress, polyphenol compounds have been shown to exert antioxidant effects directly by reacting with oxygen radicals or indirectly by activating enzyme systems such as catalase, superoxide dismutase, and myeloperoxidase (15,(28)(29)(30). It has been suggested that eckol, an ECP component, inhibits apoptosis in the cells against radiation damage by suppressing the proapoptotic p53 and Bax genes and by inducing the antiapoptotic Bcl-2 gene (30).…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cells are highly sensitive to ionizing radiation (41) . Hematopoietic recovery depends on the percentage of residual hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%